2012
DOI: 10.1371/journal.pone.0036141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Bt MON810 Maize to Pigs for 110 Days on Peripheral Immune Response and Digestive Fate of the cry1Ab Gene and Truncated Bt Toxin

Abstract: BackgroundThe objective of this study was to evaluate potential long-term (110 days) and age-specific effects of feeding genetically modified Bt maize on peripheral immune response in pigs and to determine the digestive fate of the cry1Ab gene and truncated Bt toxin.Methodology/Principal FindingsForty day old pigs (n = 40) were fed one of the following treatments: 1) isogenic maize-based diet for 110 days (isogenic); 2) Bt maize-based diet (MON810) for 110 days (Bt); 3) Isogenic maize-based diet for 30 days fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
23
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 29 publications
3
23
0
2
Order By: Relevance
“…Numerous studies have investigated the effects of Bt maize consumption on production and health characteristics in different animal species (3)(4)(5)(6)(7)(8)(9)(10); however, apart from those conducted by our group, few studies have been performed in pigs. Furthermore, while a number of studies have investigated the effects of Bt maize on the intestinal microbiota of ruminants (6,11,12), our group was the first to examine its impact on the porcine intestinal microbiota (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have investigated the effects of Bt maize consumption on production and health characteristics in different animal species (3)(4)(5)(6)(7)(8)(9)(10); however, apart from those conducted by our group, few studies have been performed in pigs. Furthermore, while a number of studies have investigated the effects of Bt maize on the intestinal microbiota of ruminants (6,11,12), our group was the first to examine its impact on the porcine intestinal microbiota (13,14).…”
mentioning
confidence: 99%
“…Such studies are warranted, considering in vitro observations that the Cry1Ab protein is antimicrobial against intestinal bacteria, such as Clostridium, both in its intact and fragmented forms, at concentrations of 25 to 63 g/ml (15). Furthermore, the Cry1Ab protein is not completely degraded during intestinal transit when administered in feed at concentrations of 0.17 to 0.52 g/g feed and persists in the intestine at concentrations of 0.003 to 0.03 g/ml (8,9,16). In addition, the finding that indigenous gut bacteria contribute to B. thuringiensis susceptibility in the larvae of some insect species (17) suggests that Bt toxins in some way impact the intestinal microbiota.…”
mentioning
confidence: 99%
“…Επιπλέον, μεγάλος όγκος μελετών έχει διεξαχθεί για τη μελέτη της θρεπτικής αξίας και της ασφάλειας των γενετικώς τροποποιημένων ζωοτροφών μετά τη χορήγησή τους σε διάφορα είδη αγροτικών ζώων (Flachowsky et al 2012). Τέλος, ικανός αριθμός άρθρων έχει δημοσιευτεί σχετικά με τύχη του 'ξένου', διαγονιδιακού ή ανασυνδυασμένου DNA των γενετικώς τροποποιημένων ζωοτροφών στο γαστρεντερικό σωλήνα των ζώων (Chainark et al, 2008, Guertler et al, 2008, Tremblay et al, 2008, Wiedermann et al, 2009, Rizzi et al, 2012, Johannessen et al, 2013, καθώς και με τις αποδόσεις παραγωγικών ζώων πού καταλώνουν τέτοιες ζωοτροφές (Alink et al, 2008, Buzoianu et al, 2012a, b, Snell et al, 2012, Walsh et al, 2012, Buzoianu et al, 2013.…”
unclassified
“…Η μελέτη αφορούσε στη χορήγηση γενετικώς τροποποιημένης τροφής σε χοιρίδια επί 110 ημέρες (Walsh et al 2012, Buzoianu et al 2012b, σε σύες στη διάρκεια της εγκυμοσύνης και της γαλακτικής περιόδου (Buzoianu et al 2012a) και σε σύες και τα χοιρίδια αυτών επί 115 ημέρες μετά τον απογαλακτισμό (Buzoianu et al 2013). ως γενικό συμπέρασμα, οι εν λόγω μελέτες κατέληξαν ότι δεν παρατηρήθηκαν ανωμαλίες στις διάφορες φυσιολογικές καταστάσεις των ζώων.…”
unclassified
“…To study possible occurrence of Cry1Ab in porcine tissues, feeding studies with PR34N44 Bt-maize were performed (WALSH et al, 2011;BUZOIANU et al, 2012;WALSH et al, 2012), and results indicated that appearance or detection success of Bt toxin in different tissues is not uniform. Cry1Ab was positively detected in stomach content and digesta samples, but fell below the LOD for other tissues.…”
mentioning
confidence: 99%